Aplikasi Analisis Tabulasi Silang (Crosstab) Dalam Perencanaan Wilayah dan Kota - Imam Indratno; Rahmat Irwinsyah (Journal of Regional and City Planning, 1998)
The field of quantitative planning analysis concerns with collecting, organizing and interpreting data to support planning processes, including analysis of category data. It is an appropriate methods to analyze discrete data. This analysis, also called as tabulation analysis, is used to determine whether the variables are related to one another or independent, and to measure the extent of their association. To use this cross tabulation analysis, the types of measurement data and the types of categorical data should be understood. This analysis is carried out by determining if the observation frequencies of occurrence of the categorical values of a qualitative could allow us to reject a hypothesis the expected frequencies of occurrence. Chi-square statistics is used to determine whether the observation frequencies differ significantly from the expected frequencies of occurrence. If computed x2 value greater than the value of x2 random variable with (r-1)(c-1)df, then the hypothesis of independent could be rejected Furthermore, to determine or measure the extent of association, we use coefficient contingency with value of O"”1.